Toxic cyanobacteria on the coast of San José, Río de la Plata, Uruguay (INNOTEC, 2024)
Dense blooms of potentially toxic cyanobacteria have been recorded on the north coast of the Río de la Plata estuary, which affect water quality for recreational or drinking water purposes. In this study we present results of a 7-years monitoring program in a coastal zone (Punta del Tigre, San José, Uruguay), with data of water temperature, conductivity, biomass and composition of cyanobacteria. The main objective was to determine the water temperature and salinity conditions associated with the dominance of cyanobacteria in the phytoplankton of the area studied. The concentration of total microcystins was quantified in selected samples. The blooms were also analyzed in satellite images based on the detection of chlorophyll a threshold. The most frequent species were potentially toxic: Microcystis aeruginosa, M. protocystis, M. novacekii, Dolichospermum circinale and D. uruguayense, often covering large areas in line with the satellite analysis. The concentrations of total microcystins generally exceeded the World Health Organization’s danger alerts for drinking water. Water temperatures above 19 °C, conductivities below 2 mS/cm and salinity below 0.5 were associated with a higher dominance of cyanobacteria in the total phytoplankton biomass. The high frequency of occurrence of these organisms in low conductivity conditions, common in the area, may compromise water quality for various uses, including human consumption.
Keywords: drinking water; water quality; estuary; blooms; microcystin